Original paperPostoperative interstitial brachytherapy in eyelid cancer: long term results and assessment of Cosmesis After Interstitial Brachytherapy scale - Laskar, Sarbani Ghosh; Basu, Trinanjan; Chaudhary, Suresh; Chaukar, Devendra; Nadkarni, Mandar; GN, Manjunatha (Journal of Contemporary Brachytherapy, 2014)
Purpose: To analyse feasibility and safety of postoperative interstitial brachytherapy (IBRT) in patients of eyelid cancer treated primarily by surgical excision. Material and methods: In this series, 8 patients with eyelid cancer were treated using postoperative interstitial brachytherapy. Patients were followed up for local control, cosmetic outcome, and acute and late toxicities. Cosmetic outcome was measured using a 6 point indigenous Cosmesis After Interstitial Brachytherapy (CAIB) scale. Results: The patients were between 23-82 years (median: 71 years). There were 3 females and 5 males, and 3 patients had lesions in upper eyelid. Postoperative high-dose-rate brachytherapy was used in all with 2 catheters implanted in most of them (6 out of 8). Local control was calculated from end of treatment to last follow-up. At last follow-up, all patients remained locally controlled. Two patients had nodal recurrence 6 months after interstitial brachytherapy and were salvaged effectively by external beam radiotherapy. At last follow-up, 7 patients were loco-regionally controlled and one was lost to follow up. All patients had Radiation Therapy Oncology Group (RTOG) grade 1 acute toxicity and 2 had grade 1 Common Terminology Criteria for Adverse Events (CTCAE) version.3 late toxicities. The cosmesis score for the whole group ranged between 0-1 indicating excellent to very good cosmesis. Conclusions : Postoperative high-dose-rate brachytherapy resulted in excellent disease control and cosmesis without significant acute or late toxicities. It is an effective modality for treatment of eyelid cancers in selected patients. Future prospective studies with the validation of CAIB scale would give us more insight to this effective yet often ignored modality of IBRT.